SOCIALIZATION OF DIAGNOSTIC E-ASSESSMENT DEVELOPMENT AS AN EFFORT TO IMPROVE TEACHER COMPETENCE IN ELEMENTARY SCHOOLS - Titin Rahmayanti Rambe; Wina Mariana Parinduri; Renni Ramadhani Lubis; Yusda Novianti; Dini Puji Anggraini; Diah Kesumawati; Sakura Alwina; Sara Frimaulia (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
The development of digital technology in education requires teachers to be competent in designing effective electronic-based assessments that meet student needs. One important form of initial assessment in the implementation of the Independent Curriculum is diagnostic e-assessment, which serves to identify students' initial abilities, knowledge gaps, and learning characteristics. This community service activity aims to improve teachers' competency in developing diagnostic e-assessments through outreach and training at Elementary School 064014 Medan. The implementation method included preparation, outreach, demonstrations of electronic-based diagnostic test preparation, and hands-on practical assistance. The results of the activity indicate an increase in teachers' understanding and skills in designing and implementing diagnostic e-assessments in their respective classrooms. This activity contributes to improving the quality of learning assessments and supports the optimal implementation of the Independent Curriculum in elementary schools.